Development and validation of an analytical method for quantification of dopamine metabolism in plasma samples by LC-MS/MS - Dias, Ana Sofia Abrantes (2017)
Dissertação de Mestrado em Química Forense apresentada à Faculdade de Ciências e Tecnologia